Critical contextual aspects of a highly complex hospital - Torres Canales, Adrián; Torres Gálvez, Álvaro; Bustamante Ubilla, Miguel; Contreras Villa, Sergio (My University, 2017)
This article presents the partial results of a SWOT analysis at the National Chest Institute, in order to generate information on critical issues affecting the strategic management of a public hospital of high complexity, and open an ethical reflection on such processes. For their determination were used: focus groups, interviews, proposed by the management team of the Hospital and discussions on the contextual level. The Individual and group interviews lasted about an hour and twenty minutes and were performed at hospital units. The conceptualization of the data was made from Grounded Theory. The study shows, according to the perception of the interviewees, their contextual issues such as rules, stakeholders and cultural country, whose ethical tension with the organization, affect the work of the National Chest Institute as a high complexity public hospital.
Aspectos críticos contextuales de un hospital de alta complejidad
Aspectos críticos contextuais de um hospital de alta complexidade
Keywords: contextual analysis; ethics tensions at public service; high complexity public hospital; impact on management; perception of stakeholders